2020
DOI: 10.1177/1088357620943506
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Question-Asking Initiations in College Students With ASD Using a Video-Feedback Intervention

Abstract: Social conversational vulnerabilities associated with autism spectrum disorders (ASDs) generally persist into young adulthood and have a detrimental impact on short- and long-term academic, vocational, and interpersonal success. In light of these challenges, there is a growing need for targeted interventions to improve the social competencies of this population. The current study examined the effects of a video-feedback intervention that targeted a key social conversational skill—making social initiations to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Given that individuals with ASD may perseverate on topics and are less likely to initiate and respond to conversational exchanges (Ying Sng et al, 2018), teaching skills necessary for reciprocal conversation is important. We agree with other researchers (Detar & Vernon, 2020; Gregori et al, 2022; Plavnick & Dueñas, 2018) who have noted that question asking skills is one discrete skill within the broader goal of effective conversation skills and social competence. However, this is the first study that has used I-Connect to teach social communication skills and represents an initial inquiry into this area.…”
Section: Importance Of Community-based Instructionsupporting
confidence: 90%
“…Given that individuals with ASD may perseverate on topics and are less likely to initiate and respond to conversational exchanges (Ying Sng et al, 2018), teaching skills necessary for reciprocal conversation is important. We agree with other researchers (Detar & Vernon, 2020; Gregori et al, 2022; Plavnick & Dueñas, 2018) who have noted that question asking skills is one discrete skill within the broader goal of effective conversation skills and social competence. However, this is the first study that has used I-Connect to teach social communication skills and represents an initial inquiry into this area.…”
Section: Importance Of Community-based Instructionsupporting
confidence: 90%
“…Two teams reported the use of self-monitoring strategies (Pennington et al, 2014; Smith, 2015). One team provided participants the opportunity to review video recording performances (Detar, 2013), and one reported to check in with participants to provide opportunities to analyze their performance (Robinson, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…One half of the investigative teams ( n = 4) calculated an effect size measure. All four of the studies used an effect size measure that was determined by overlapping methods (Detar, 2013, such as PND (percentage of non-overlapping data; Mason et al, 2012; Smith et al 2019) or IRD (improvement rate difference; Smith, 2015). Detar also reported using an additional effect size measure, Cohen’s d .…”
Section: Discussionmentioning
confidence: 99%
“…Psycho-educational techniques, such as video-feedback interventions, were shown to be a reliable method to help individuals with ASD decode social cues and improve their social skills, such as engaging in conversation or being empathetic and reciprocal. Therefore, these techniques could be used to increase socially appropriate behaviors during social interactions (e.g., [ 74 , 75 ]). However, there is an ongoing debate regarding how to teach social skills most effectively (e.g., [ 76 ]), and whether training social skills may have long-term negative effects, including increased camouflage (e.g., [ 77 ]).…”
Section: Discussionmentioning
confidence: 99%